If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 6 = 8 + 3y Reorder the terms: 6 + 2y = 8 + 3y Solving 6 + 2y = 8 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 6 + 2y + -3y = 8 + 3y + -3y Combine like terms: 2y + -3y = -1y 6 + -1y = 8 + 3y + -3y Combine like terms: 3y + -3y = 0 6 + -1y = 8 + 0 6 + -1y = 8 Add '-6' to each side of the equation. 6 + -6 + -1y = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 8 + -6 -1y = 8 + -6 Combine like terms: 8 + -6 = 2 -1y = 2 Divide each side by '-1'. y = -2 Simplifying y = -2
| (x-2)(3x+5)= | | -10/x=5/x-10/3 | | x-255=443 | | 46=3u-11 | | 600=2500(X)(4) | | (5x-2)/2x-18 | | 4n-6.4=2(n+1.3) | | (5x-2)/2x-18=0 | | x+255=433 | | 6x^2+7x-2= | | -4r+12=-72 | | 4/840=4/x | | 4/3x-2=16 | | 840/x=3/4 | | 3x-5(-2+3x)=10 | | r^2+69r-216=0 | | 2/7t-10/7t | | x-0.7=8.59 | | 0=-16t+vt+16 | | 11A-13=-7A^2 | | j^2-20j+36=0 | | 0=(x-9)(3x+1) | | 3/840=4/x | | n-3/4=5/12 | | 3m-2(m+7)=m-14 | | log(2x)+log(x)=11 | | n-3/4 | | (48w^9x^3/3w^5x^5)^1/2 | | -7(t+5)=14 | | 4/5x=2 | | -4x=-18+5x | | (5x^0/10x^-3y^2)^2 |